Spin transition of ferropericlase under shock compression - N. B. Zhang; Y. Cai; X. H. Yao; X. M. Zhou; Y. Y. Li; C. J. Song; X. Y. Qin; S. N. Luo (AIP Advances, 2018)
Planar shock compression experiments are performed at 9–105 GPa on polycrystalline ferropericlase (Mg0.94Fe0.06)O to investigate its Fe2+ spin transition. Forward and reverse impact configurations are used to obtain Hugoniot and shock-state sound velocities. While wave profiles, shock velocity–particle velocity and pressure–density measurements show negligible/weak indications of a phase transition, the shock-state sound speed data clearly manifest a phase transition in the range of 36–62 GPa at the nanosecond time scales. These shock data reveal the phase transition as the spin transition identified in static compression experiments and first-principles calculations.